Pengaruh Pendapatan Asli Daerah, Opini Audit, Dan Belanja Modal Terhadap Kinerja Keuangan Pemerintah Daerah - Fatimah Az Zahrah; Muhammad Rafi Zaen; Salma Putri Mellinia (Pusat Riset dan Inovasi Nasional, 2024)
The research aims to determine and analyze the influence of local revenue, audit opinions and capital expenditure on regional financial performance in districts/cities in East Java province. The data processed is secondary data taken from the 2018-2021 District/City Regional Government Financial Reports (LKPD) of East Java Province with a sample size of 38 districts/cities using the documentation method. The method used in this research is the panel data regression analysis method using the IBM SPSS version 26 application. The research results found that local revenue has a positive and significant effect on local government financial performance, audit opinion has a positive but not significant effect on local government financial performance, and capital expenditure has no and no significant effect on local government financial performance.